The silent codon change I507‐ATC→ATT contributes to the severity of the ΔF508 CFTR channel dysfunction. Issue 11 (1st August 2013) - Lazrak, Ahmed; Fu, Lianwu; Bali, Vedrana; Bartoszewski, Rafal; Rab, Andras; Havasi, Viktoria; Keiles, Steve; Kappes, John; Kumar, Ranjit; Lefkowitz, Elliot; Sorscher, Eric J.; Matalon, Sadis; et al.
Abstract : The most common disease‐causing mutation in the cystic fibrosis transmembrane conductance regulator (CFTR) gene is the out‐of‐frame deletion of 3 nucleotides (CTT). This mutation leads to the loss of phenylalanine‐508 (ΔF508) and a silent codon change (SCC) for isoleucine‐507 (I507‐ATC→ATT). ΔF508 CFTR is misfolded and degraded by endoplasmic reticulum‐associated degradation (ERAD). We have demonstrated that the I507‐ATC→ATT SCC alters ΔF508 CFTR mRNA structure and translation dynamics. By comparing the biochemical and functional properties of the I507‐ATT and I507‐ATC ΔF508 CFTR, we establish that the I507‐ATC→ATT SCC contributes to the cotranslational misfolding, ERAD, and to the functional defects associated with ΔF508 CFTR We demonstrate that the I507‐ATC ΔF508 CFTR is less susceptible to the ER quality‐control machinery during translation than the I507‐ATT, although 27°C correction is necessary for sufficient cell‐surface expression. Whole‐cell patch‐clamp recordings indicate sustained, thermally stable cAMP‐activated Cl – transport through I507‐ATC and unstable function of the I507‐ATT ΔF508 CFTR Single‐channel recordings reveal improved gating properties of the I507‐ATC compared to I507‐ATT ΔF508 CFTR ( NPo =0.45±0.037 vs. NPo =0.09±0.002; P <0.001). Our results signify the role of the I507‐ATC→ATT SCC in the ΔF508 CFTR defects and support the importance of synonymous codon choices in determining the function of gene products.—Lazrak, A., Fu, L., Bali, V., Bartoszewski, R., Rab, A., Havasi, V., Keiles, S., Kappes, J., Kumar, R., Lefkowitz, E., Sorscher, E. J., Matalon, S., Collawn, J. F., Bebok, Z. The silent codon change I507‐ATC→ATT contributes to the severity of the ΔF508 CFTR FASEB J . 27, 4630–4645 (2013). www.fasebj.org